Synthesis, Structure, and Magnetic Properties of a Mononuclear Chiral (Acetato)bis(aminoalkoxido)manganese(III) Complex. Issue 10 (15th March 2017) - Kornowicz, Arkadiusz; Terlecki, Michał; Prochowicz, Daniel; Pichon, Céline; Justyniak, Iwona; Bury, Wojciech; Wróbel, Zbigniew; Sutter, Jean‐Pascal; Lewiński, Janusz
Abstract : A new synthetic procedure was developed to obtain a novel mononuclear chiral square‐pyramidal (acetato)bis(aminoalkoxido)Mn III complex from a heterometallic Zn II /Mn II system with a crucial role for O2 in the process. The resulting compound was characterized spectroscopically and crystallographically, and its magnetic properties were determined. The Mn III ion exhibits magnetic anisotropy with a zero‐field splitting D parameter equal to –2.95 cm –1 . Abstract : A new synthetic procedure is developed to obtain a novel mononuclear chiral square‐pyramidal (acetato)bis(aminoalkoxideo)Mn III complex. The resulting compound is characterized spectroscopically and crystallographically, and its magnetic properties are determined.